Grassroots to Global: The Future of Nursing Leadership. (March 2019) - Nelson-Brantley, Heather V.; David Bailey, K.; Batcheller, Joyce; Bernard, Noreen; Caramanica, Laura; Snow, Francine
Abstract : The 2018 International Nursing Administration Research Conference, Grassroots to Global, was held in Atlanta, Georgia, with attendees from 38 US states, Canada, and China. Presenters discussed the need for nurse leaders to be prepared to partner with those inside and outside of healthcare to create innovative, interprofessional care delivery models; advocate for advancements in technology to address healthcare access shortages; and lead new areas of research that can drive policy change to support nurse leaders in long-term care and the essential role of the nurse manager in creating optimal practice environments for quality outcomes. This article will report on these important insights.